OPTIMALISASI MEDIA DAKWAH DIGITAL BAGI KOMUNITAS MUSLIM: PENDEKATAN EDUKASI - Kahfi, Shofiyullahul; Za’im Muhibbullah, Muhammad (Department of Da'wah Management, Faculty of Da'wah, IAINU Tuban, 2024)
Optimization of Digital Da'wah Media with an Educational Approach for the Muslim Community is an important effort to enhance understanding and engagement with Islamic teachings in the digital era. This study aims to analyze various strategies and content used in digital da'wah media to achieve educational objectives. The methodology employed is a qualitative approach with Library Research. The analyzed data includes types of content, delivery formats, and user interactions with the content. The results indicate that content on social media in the form of videos, infographics, and educational articles has a high appeal and can significantly enhance audience understanding, particularly among the youth. Additionally, the use of simple language and engaging presentation contributes to the effectiveness of message delivery. The conclusion of this study emphasizes that the optimization of digitalda'wah media with an educational approach can strengthen the understanding of Islamic teachings and encourage active participation within the Muslim community. Therefore, da'wah managers need to continuously innovate in creating relevant and engaging content to reach a broader audience.